1991
DOI: 10.1037/h0089149
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents in end-stage renal failure: A pilot study of family factors in compliance and treatment considerations.

Abstract: This article consists of two parts. In the first, we present the findings of a pilot study of six families with an adolescent with end-stage renal disease. In the second, we describe four families and the role of the family therapist in their treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…There is evidence that children do not ‘comply’ (Korsch et al. 1978, Altschuler et al. 1991, Meyers et al.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that children do not ‘comply’ (Korsch et al. 1978, Altschuler et al. 1991, Meyers et al.…”
Section: Introductionmentioning
confidence: 99%
“…This factor should be researched further. Other researchers investigating compliance and hostility (Altschuler, Black, Trompeter, Fitzpatrick, & Peto, 1991;Flanagan & Wagner, 1991;Gould et al, 1985;LeFave, 1980;Pugh, 1983) have found a range of effect sizes. However, these studies measured total hostility rather than distinguishing intrapunitive from extrapunitive hostility.…”
Section: General Hypothesismentioning
confidence: 93%
“…(3) race [5,8,13,15]; (4) socioeconomic status [5,17,18]; (5) family communication difficulties [14]; and (6) family instability or enmeshment [9,19].…”
Section: Introductionmentioning
confidence: 99%